Prophylaxis of postoperative complications after craniotomy. Issue 5 (October 2017) - Tsaousi, Georgia G.; Pourzitaki, Chryssa; Bilotta, Federico
Abstract : Purpose of review: This review reports an update of the evidence on practices applied for the prevention and management of the most common complications after craniotomy surgery. Recent findings: Latest guidelines support the combined thromboprophylaxis with the use of both mechanical and chemical modalities, preferably applied within 24 h after craniotomy. Nevertheless, a heightened risk of minor hemorrhagic events remains an issue of concern. Postoperative nausea and vomiting (PONV) and pain constitute the complications most commonly encountered during the first 24 h postcraniotomy. Recently, neurokinin type-1 receptor antagonists have been tested as adjuncts for PONV prophylaxis with encouraging results, whereas dexmedetomidine and gabapentinoids emerge as promising alternatives for postcraniotomy pain management. The available data for seizure prophylaxis following craniotomy lacks scientific quality; thus, this remains still a debatable issue. Significantly, a growing body of evidence supports the superiority of levetiracetam over the older antiepileptic drugs (AEDs), in terms of efficacy and safety. Summary: Optimum management of postoperative complications is incorporated as an integral part of the augmented quality of care in patients undergoing craniotomy surgery, aiming to improve outcomes. This review may serve as a benchmark for neuroanesthetists for heightened clinical awareness and prompt institution of well-documented practices.